Bottom-up processing of curvilinear visual features is sufficient for animate/inanimate object categorization - Zachariou, Valentinos (J Vis, 2018)
Animate and inanimate objects differ in their intermediate visual features. For instance, animate objects tend to be more curvilinear compared to inanimate objects (e.g., Levin, Takarae, Miner, & Keil, 2001). Recently, it has been demonstrated that these differences in the intermediate visual features of animate and inanimate objects are sufficient for categorization: Human participants viewing synthesized images of animate and inanimate objects that differ largely in the amount of these visual features classify objects as animate/inanimate significantly above chance (Long, Stormer, & Alvarez, 2017). A remaining question, however, is whether the observed categorization is a consequence of top-down cognitive strategies (e.g., rectangular shapes are less likely to be animals) or a consequence of bottom-up processing of their intermediate visual features, per se, in the absence of top-down cognitive strategies. To address this issue, we repeated the classification experiment of Long et al. (2017) but, unlike Long et al. (2017), matched the synthesized images, on average, in the amount of image-based and perceived curvilinear and rectilinear information. Additionally, in our synthesized images, global shape information was not preserved, and the images appeared as texture patterns. These changes prevented participants from using top-down cognitive strategies to perform the task. During the experiment, participants were presented with these synthesized, texture-like animate and inanimate images and, on each trial, were required to classify them as either animate or inanimate with no feedback given. Participants were told that these synthesized images depicted abstract art patterns. We found that participants still classified the synthesized stimuli significantly above chance even though they were unaware of their classification performance. For both object categories, participants depended more on the curvilinear and less on the rectilinear, image-based information present in the stimuli for classification. Surprisingly, the stimuli most consistently classified as animate were the most dangerous animals in our sample of images. We conclude that bottom-up processing of intermediate features present in the visual input is sufficient for animate/inanimate object categorization and that these features may convey information associated with the affective content of the visual stimuli.